Solvent effect on the phenolic compounds and biological activity of difference Morinda citrifolia root extract - Idris Adewale Ahmed,; Fasihuddin Badruddin Ahmad,; Cheng, Gwendoline Lian Ee; Siau, Hui Mah; Nor Hisam Zamakshshari, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Cancer and antimicrobial resistance have become a threat to global health and development. This work aimed to identify the biological activities and phenolic compounds content of different Morinda citrifolia L. root extracts. The relationship between biological activities and phenolic content was also discussed. All extracts were screened for antioxidant activity using anti-oxidant assays (FRAP, DPPH, TAOC, ABTS, and BCB) and quantitative phytochemical analyses (TPC). Antimicrobial activity against four bacterial and two fungal strains as well as cytotoxic activities on stomach cancer (SNU-1), colon cancer (LS-174T and HT29), leukemia (K562), and breast cancer (MDA-MB-361) cell lines were also performed. With a value of 122.789 g of gallic acid equivalent/mg extract,the dichloromethane extract had the highest total phenolic content (TPC). The extract also showed high antioxidant activities in all the antioxidant assays and antimicrobial activity. The FRAP (r2 = 0.962) as well as antimicrobial activities against Staphylococcus aureus (r2 = 0.708), Bacillus subtilis (r2 = 0.890) and Pseudomonas aeruginosa (r2 = 0.870) were strongly correlated with the total phenolic content. The LS-174T, K562, HT-29, and MDA-MB-361 cytotoxic activities were also strongly correlated with the total phenolic content with r2 = -0.899, -0.845, -0.981, and -0.978, respectively. The results obtained suggested that the dichloromethane extract of Morinda citrifolia has high biological activity compared to other extracts.